Effect of Rectangular Ribs in the Flow Channels of HTPEM Fuel Cell by a Three-dimensional Model. (May 2017) - Wu, Horng-Wen; Kang, Duo-Yao; Perng, Shiang-Wuu
Abstract: This paper employs a three-dimensional model to study the cell performance of HTPEM (high temperature proton exchange membrane) fuel cells using rectangular ribs with various numbers transversely inserted at the axis in the anode and cathode channels, and determines the higher net cell power. The results show that the best net cell power occurs as the number of rectangular ribs is five, and the net cell power for five rectangular ribs is higher than that for without rib by 6.6%.